2020
DOI: 10.21203/rs.3.rs-95107/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional Lymph Nodes Distribution Pattern in Central Area of Right-sided Colon Cancer: In-Vivo Detection and the Update on the Clinical Exploration.

Abstract: BackgroundDistribution of regional lymph nodes (LNs) is decisive for the lymphadenectomy boundary in radical resection of a right-sided colon cancer (RCC). Currently, the data of LNs in central area remains ambiguous and scarce. Herein we aim to provide a more detailed anatomical research on LNs surrounding the superior mesenteric vessels for RCC and investigated the metastasis rate.MethodsCarbon Nanoparticles (CNs) or Indocyanine Green (ICG) were used as dye and we laparoscopically observed the stained LNs di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…However, the dissection of lymph nodes on the SMA surface led to severe chylous ascites. Moreover, previous studies have shown that lymph node dissection damages autonomic nerves and leads to gastrointestinal dysfunction [ 10 ]. In clinical practice, we found a high incidence of chylous ascites after right colectomy; After completing this manuscript, we studied the risk factors of chylous ascites with curiosity and published it before the acceptance of this article [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the dissection of lymph nodes on the SMA surface led to severe chylous ascites. Moreover, previous studies have shown that lymph node dissection damages autonomic nerves and leads to gastrointestinal dysfunction [ 10 ]. In clinical practice, we found a high incidence of chylous ascites after right colectomy; After completing this manuscript, we studied the risk factors of chylous ascites with curiosity and published it before the acceptance of this article [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different surgical methods and surgical ranges for right colon cancer have been used, and these have led to different incidences of postoperative complications, including complete mesocolic excision (CME) and D3 lymph node dissection, standard operation and extended right colectomy, and differences in the medial boundary of lymph node dissection [9][10][11]. Currently, few studies on risk factors for EPSBO after right hemicolectomy have been reported, especially to establish predictive models.…”
Section: Introductionmentioning
confidence: 99%
“…According to existing research, age, tumor location, tumor size and T stage had been shown to affect LNM in colorectal cancer 17,29,30 Cancer risk communication in sensitivity and speci city for preoperative N stage remains di cult when compared to T stage because differentiating between malignant and reactive lymph node enlargement is di cult 34 . Therefore, studies have aimed at improving the detection rate for positive lymph nodes [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…It is a favorable fluorescence nanoprobe owing to its strong near-infrared (NIR) fluorescence emission and optimal photothermal capabilities . Thus, it can be potentially used in the photothermal and photodynamic tumor therapies . However, its diagnostic and therapeutic applications are seriously impeded by its limitations, viz., aggregation and decomposition in the polar solvents, instability in the aqueous solutions, rapid clearance in the plasma medium (half-life: 2–4 min), poor tumor-targeting ability, etc .…”
Section: Introductionmentioning
confidence: 99%
“…9 Thus, it can be potentially used in the photothermal and photodynamic tumor therapies. 10 However, its diagnostic and therapeutic applications are seriously impeded by its limitations, viz., aggregation and decomposition in the polar solvents, instability in the aqueous solutions, rapid clearance in the plasma medium (half-life: 2−4 min), poor tumor-targeting ability, etc. 11 Therefore, a smart design of the ICG-loaded system is urgently needed for the targeted delivery of ICG during the light-activated combination cancer therapy.…”
Section: ■ Introductionmentioning
confidence: 99%